2014
DOI: 10.1021/ef402101s
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Bitumen from Oil Sands

Abstract: In the present study, solvent extraction of bitumen from Xinjiang oil sands was investigated using solvents, such as alkanes, toluene, and chloroform, and mixed solvents, such as n-hexane–ethyl acetate and cyclohexane–methyl ethyl ketone (MEK). The n-heptane asphaltene content in the extracted bitumen was measured by saturate, aromatic, resin, and asphaltene (SARA) analysis, and the average molar mass of asphaltene was tested by vapor pressure osmometry (VPO). The average molar mass of asphaltene was 2850, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 14 publications
1
57
0
Order By: Relevance
“…The smaller χ p-s indicates the higher interaction between the polymer and the solvent41. The δ values of PS, PMMA and toluene are 18.6, 19.2 and 18.2 MPa 1/2 , respectively4243. Based on equation (1), the χ p-s of PS and toluene is smaller than χ p-s of PMMA and toluene, which implies that toluene is better solvent for PS than for PMMA.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller χ p-s indicates the higher interaction between the polymer and the solvent41. The δ values of PS, PMMA and toluene are 18.6, 19.2 and 18.2 MPa 1/2 , respectively4243. Based on equation (1), the χ p-s of PS and toluene is smaller than χ p-s of PMMA and toluene, which implies that toluene is better solvent for PS than for PMMA.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable research has been performed in an effort to separate bitumen from oil sands using solvent extraction [5] [6]. Several process were suggested to slurry the oil sands in one or multiple non-aqueous solvents followed by filtration and then separation of the solvent from the sand tailings [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the theory of Hanson solubility, good solvents always possess parameter distributions (i.e., dispersion force, polar force, and hydrogenbonding force) in a specific range depending upon the solute (Hansen, 2007). Wang et al (2014) reported good solvents for the dissolution of bitumen generally have relatively high values for δ d and δ h and a low value for δ p .…”
Section: Techniques For Treating Oily Sludgementioning
confidence: 97%
“…Therefore, in the solvent extraction of oil from oily sludge, the dissolving capacity of solvent is a combination of the Hildebrand solubility parameter ( δ ), and the parameter distribution of the acting force parameter (δ d , δ p , and δ h ). According to Wang et al (2014), a solvent with a solubility parameter close to that of asphaltene and a parameter distribution close to that of toluene is desirable for the bitumen recovery from oil sands.…”
Section: Techniques For Treating Oily Sludgementioning
confidence: 99%
See 1 more Smart Citation